The emerging applications of pillararene architectures in supramolecular catalysis - Wang, Kaiya; Tian, Xueqi; Jordan, Jacobs H.; Velmurugan, Krishnasamy; Wang, Leyong; Hu, Xiao-Yu (Chinese chemical letters, 2022)
Over the last decade, numerous research efforts have been devoted to pillar[n]arenes since their debut. The popularity of pillararenes is a reflection of current research trend in supramolecular and macrocyclic chemistry in general. Among the vast applications (such as chemosensors, drug delivery, transmembrance channels, and separation) of pillararenes, their utilization in catalysis is a relatively less explored area. However, soaring attention has been paid by researchers in recent years and this field has seen gradual increasing publications. Therefore, in this review we will discuss progress in the emerging applications of pillararene architectures in catalysis based on various reaction genre including reduction, oxidation, coupling, decomposition and others. Furthermore, this review not only focuses on the pillararenes based current progress in catalysis, but also provides the signs for future development in this research field. [Display omitted]